English Students Association (ESA) for Developing The English Skills of English Education Department Students in STAIN KUDUS - Suciati, Suciati (Journal of English Teaching and Learning Issues, 2019)
This study aims to identify the role of English Students Association (ESA) in developing English Skills of English Education Department (EED) students, identify the factors influencing the students to develop their English Skills in ESA and find the solution for the problems. This descriptive qualitative study was conducted in STAIN Kudus, especially focus on ESA programs or activities. The participants of this research were the students of EED STAIN Kudus who join ESA. The data were collected through observation, interview, and documentation analysis. There were three results. First, the role of ESA in developing English skills of EED students is important and very big, especially for improving their speaking skills (listening, speaking, reading, and writing). Second, there are internal and external factors influencing the EED students to develop their English Skills in ESA. The internal factors are students’ self motivation and character.  And the external factors are environment (class or other friends’ condition/influence), syllabus/lesson plan, materials/programs, teaching technique/strategy, level of regulation, and several agenda/programs in the same time. And third, solutions for the problems are the existence of clear organization structure and regulation, well-organized materials/class, interesting and fun programs, students and lecturers’ support and appreciation.